Can HRV biofeedback improve short-term effort recovery? Implications for intermittent load sports - Perez-Gaido, M.; Lalanza, J. F. L.; Parrado, E.; Capdevila, L. (Applied Psychophysiology and Biofeedback, 2021)
As intensity and physical demands continue to rise in sport competition, faster and better recovery becomes essential. The aim of this study was to assess the effects of HRV biofeedback (HRVB) while recovering from a submaximal aerobic exer-cise. Ten physically-active graduate students participated in the study, which was conducted in four sessions: exercise with free-breathing recovery, first resonance frequency (RF) detection, second RF detection, and exercise applying HRVB during recovery. Measurements included time spent running and recovering, HRV parameters, and recovery/exertion perceptions. The results indicate that using HRVB during recovery improves cardiac variability (RRmean, SDNN, RMSSD and LF; p<0.01). HRVB also lowers recovery time (p<0.05) and seems to be improving the perception of recovery (p=0.087). Moreover, time spent exercising (p<0.01) and perceived physical exertion (p<0.05) were higher when applying HRVB. The improvement in the psychophysiological adaptation after intensive aerobic exercise provided by the HRVB is a valuable benefit, not only for competition-driven athletes, but also for the general population.